Understanding the Psychosocial Profile of Women with Fibromyalgia Syndrome - Jill Shuster; Jana McCormack; Rebecca Pillai Riddell; Maggie E Toplak (Pain Research and Management)
Fibromyalgia syndrome (FMS) is a disease with a complex etiology characterized by symptoms of widespread pain and fatigue. FMS is more common in women. Both depression and anxiety have been found to be independently associated with the severity of pain in symptoms of FMS. The goal of the present study was to examine the psychosocial profile of women with FMS and to see how the attributions, perceived social support and cognitive biases of women with FMS are related to internalizing ratings of depression and anxiety. The current study included a sample of women with FMS from a local support group and a control group to examine how women with FMS differed from controls with respect to psychosocial variables, and to determine the relationship between these variables. Women with FMS reported a higher external locus of control, lower levels of adaptive cognitive bias, less perceived family support and lower mood than controls. Correlations between these variables were examined within the FMS group, and it was found that an external locus of control was significantly associated with higher ratings of anxiety and depressed mood. These results suggest that beliefs about locus of control and perceived family support of women with FMS may importantly impact their health outcomes, and that treatments related to locus of control and advocating for family support may considerably improve the quality of life of patients with FMS.